Effect of Simulation-based Practice by applying Problem based Learning on Problem Solving Process, Self-confidence in Clinical Performance and Nursing Competence - Young A Song (Korean Society of Women Health Nursing, 2014)
PURPOSE: The purpose of this study was to analyze the effectiveness of simulation-based maternity nursing practice by applying problem based learning (PBL) on the problem solving process, self-confidence in clinical performance and nursing competence of nursing students. METHODS: This study was one group pre-posttest design, with 123 third year nursing students. Data were collected from March 19 to May 29, 2013 as the students completed their simulation practice class. Students completed a survey about their problem solving process, self-confidence, and nursing competence at the beginning and the end of the class. RESULTS: Students' problem solving process, self-confidence, and nursing competence showed significant improvements after the simulation-based maternity nursing practice. CONCLUSION: Therefore, it is recommended that current maternity nursing curriculum should be reviewed and improved, and the students should be provided variety of simulation-based education and maternity nursing skills.